Порядок і строк апеляційного оскарження судового рішення у цивільному процесі України - Теремецький, В. І.; Teremetskyi, V. I.; Батрин, О. В.; Batryn, O. V. (Право і безпека. - 2013. - № 2 (49). - С. 189-194, 2013)
Розглянуто процесуальний порядок подання апеляційної скарги у цивільному судочинстві України. Зроблено висновок, що збільшення строку апеляційного оскарження в цивільному процесі відповідатиме таким правовим категоріям правосуддя, як ефективність і допустимість. Запропонована передбачити в ЦПК України вимогу, що порушення встановленого порядку подання апеляційної скарги є підставою для її повернення суду, що ухвалив оскаржуване рішення.

The article is devoted to the research of the appeal filing and terms to appeal a judgment in the domestic civil proceedings. The aim of the paper is to study the procedure of the appeal filing and the terms within which a person may appeal a judgment in civil proceedings. Another aim of the paper is to make suggestions to the Civil Procedural Code of Ukraine to solve certain issues that arise in practice under realizing the right of appeal by a person. Formal and legal and dialectical methods were used in defining the notion «the term of an appeal», namely this notion must mean a result of a compromise concerning the need to create conditions, where the right to appeal is not limited. Comparative and legal method was used under the analysis of the procedure of the appeal filing to the Court of Appeal within the legislation of European countries. It is indicated that it is necessary to include a requirement that a violation of the set procedure of appeal filing to the Civil Procedural Code of Ukraine has to be a reason of its return to the court, which made this decision. The author agrees with the position of the Constitutional Court of Ukraine that shortening of the appeal terms is not a limitation of constitutional human rights and freedoms, but it is fixation of these rights and freedoms’ limits. However, it is emphasized that reducing the terms of an appeal causes difficulties for people while appealing judgments, which, in their opinion, are not grounded or illegal. It is concluded that the increase of the terms to appeal may reduce the number of complaints due to the fact that a person filing the appeal will be able to examine properly the reasoning of the court’s decision. It is stressed that a large number of appeals are filed rather hastily in the absence of the entire text of the judgment so as not to miss the opportunity to appeal the judgment in the specified terms. It is found out that the terms of appeal, which would meet the requirements of expediency and thus, guaranteeing the right of appeal shall be 15 days for the decisions of the first instance courts and 10 days for the orders of the first instance courts.

Рассмотрен процессуальный порядок подачи апелляционной жалобы в гражданском судопроизводстве Украины. Сделан вывод, что увеличение срока апелляционного обжалования в гражданском процессе будет отвечать таким правовым категориям правосудия, как эффективность и допустимость. Предложено предусмотреть в ГПК Украины требование: нарушение установленного порядка подачи апелляционной жалобы является основанием для её возвращения суду, постановившему обжалуемое решение.
The procedure and terms to appeal a judgment in civil proceedings of Ukraine
Порядок и срок апелляционного обжалования судебного решения в гражданском процессе Украины
Keywords: апеляційна скарга; цивільне судочинство; строк апеляційного оскарження; право апеляційного оскарження; appeal; civil judiciary; term of appeal; right to appeal; апелляционная жалоба; гражданское судопроизводство; срок апелляционного обжалования; право апелляционного обжалования